THE INFLUENCE BOILING OF FRAGRANT PANDAN AND CINNAMON TO REDUCING BLOOD GLUCOSE LEVELS IN DIABETES MELLITUS - Zahroh, Roihatul; Istiroha, Istiroha; Suwanto, Suwanto; Dewi Zulfiatu Rohmah, Dewi Zulfiatu Rohma (jfpublisher, 2023)
Introduction. Diabetes mellitus is a metabolic disease characterized by high levels of glucose in the blood, if not treated many body systems can be damaged, especially nerves and blood vessels. The purpose of this study was to explain the effect of pandan leaves and cinnamon decoction on random blood glucose reduction in patients with diabetes mellitus. Method.This research design uses Quasy-Experimental with a pre post test control group design approach. The study population was 35 respondents in Gurangwetan Hamlet. In the selection of samples using purposive sampling method which amounted to 32 respondents. The independent variable in this study is a decoction of fragrant pandanus and cinnamon, while the dependent variable is random blood glucose levels in patients with diabetes mellitus. Instruments used SOP fragrant pandanus and cinnamon decoction, observation sheet, Glucose meter (Esay touch). Data analysis using the Wilcoxon Signed Rank Test and Mann Whitney U-test. Result & Analysis. The results of the Wilcoxon Signed Rank Test statistical test of random blood glucose in the intervention group (p=0.001) means that there is an effect of fragrant pandanus and cinnamon decoction on reducing random blood glucose levels, in the control group (p=0.008) means that there is a difference in random blood glucose levels before and after intervention. Discussion. The results of the Mann Whitney U-test showed no difference in the intervention and control groups after being given the intervention to reduce random blood glucose levels (p=0.382). Discussion. The intervention of fragrant pandanus and cinnamon decoction has the same effectiveness as pharmacological drugs that can reduce random blood glucose levels, so this complementary therapy of fragrant pandanus and cinnamon decoction can be used as a companion therapy for people with diabetes mellitus.